The Effect of Bidens pilosa Extract on Vancomycin-Induced Acute Kidney Injury in Prepubertal Rats - Priawan, Indra; Harahap, Armansyah Maulana; Siregar, Sarah Rahmayani (Fakultas Kedokteran Universitas Malikussaleh, 2024)
The long-term use of Vancomycin and its administration at inappropriate doses still cause uncontrolled physiological side effects, particularly in terms of kidney development and metabolism. This study aims to investigate the effects of Bidens pilosa extract (BPE) on vancomycin-induced acute kidney injury in prepubertal rats. This study employed an experimental research method, randomly dividing 40 female Wistar rats into five equal groups: control/adult (C), prepubertal (P), prepubertal + Bidens pilosa (PB), prepubertal + vancomycin (PV), and prepubertal + vancomycin + Bidens pilosa (PVB). Gentamicin caused kidney damage in both PG and PVB groups. We treated PB and PVB with a single dose of BPE. At necropsy, we collected blood, serum, and kidney tissue for evaluation. The research results showed that the total leukocyte count was higher in PB compared to the others (P = 0.002). Serum urea, creatinine, aspartate aminotransferase, and total protein levels significantly increased in PB, PV, and PVB compared to C and P. Glutathione levels were low in the serum and kidney tissue of PV, and malondialdehyde levels were high compared to the others (P<0.05). Using BPE in vancomycin-induced acute kidney injury in ovariectomized rats resulted in a decrease in serum creatinine, urea, and malondialdehyde levels in PVB compared to PV, an increase in glutathione levels, and a milder severity of histopathological findings. The conclusion of this study shows that a single dose of BPE partially reduces kidney damage in rats with gentamicin-induced acute kidney injury